IMPROVING STUDENT SPEAKING SKILLS USING THE HELLO ENGLISH APPLICATION - Anggraini; Faisal; Unpris Yastanti (Journey: Journal of English Language and Pedagogy, 2023)
Currently, the development of technology is very advanced. Technology can be used as an alternative to other media to gain learning about various English skills. With an application that can be used as a medium for learning English, of course, it will be very helpful for the general public or students who want to learn English instantly. One of the language skills that are very important in everyday life is speaking skills as an effective oral communication medium. The researcher used classroom action research to do this research. which aims to improve students' speaking skills using the Hello English application. This research was conducted in two cycles. The research procedure in this study consisted of four steps. Namely planning, implementation, observation, and reflection. Research instruments are in the form of observation sheets, questionnaires, tests, and documentation. From the findings and discussion, it is found that the Hello English application can improve students' speaking skills. This can be seen in test cycle 2. In cycle 2, the students' speaking scores showed that 20 students passed and 2 students failed. The average test score in cycle 2 was 8.05 and the percentage increase was 85.25%. This shows that in cycle 2 the student's score meets the success criteria of 75%. Thus, based on the results of cycle 2 the Hello English application can improve student’s speaking skills.